Publishers’ and editors’ perceptions of equity, diversity, and inclusion: A cross-sectional study of European Association of Science Editors’ community - Shelly Melissa Pranić; Ana Heredia; Charikleia Tzanakou; Pavel Ovseiko; Kate Wilson; Diana Samuel; Christina Kassiteridi (European Science Editing)
Background: Scholarly settings lack racial, ethnic, sex, gender, geographic, and linguistic diversity. Despite initiatives to promote more inclusive scholarly com-munities, the extent of implementation of policies related to equity, diversity, and inclusion (EDI) remains low.Objectives: The objective is to survey the perceptions and opinions of journal editors and other stakeholders with reference to policies related to EDI and relevant prac-tices in their journals and organizations.Methods: We sent out, through email, a link to a survey with 16 Likert-scale items and 8 open-ended questions in English to assess the perceptions of EDI. Questions were generated based on discussions at meetings of the European Association of Science Editors (EASE) EDI Committee in November and December 2023. The survey was available from 8 to 30 January 2024. Snowball sampling was used among members of EASE and those of related professional organizations recruited through social networks.Results: Of the total of 232 participants, 129/232 (56%) responded on behalf of jour-nals and 103/232 (44%) on behalf of organizations. Most (72%) considered EDI to be important or very important for their journal or organization, and even more (76%) wanted examples of existing policies and guidelines for implementing EDI. Exactly 50% (27/54) reported that their organizations have no published EDI policies, and 59% (54/91) reported the absence of an EDI statement.Conclusion: Although the survey showed wide support for EDI within journals and organizations, efforts to develop EDI policies and statements have been limited, as reflected in the responses that welcomed guidance on EDI. This suggests a need for increased awareness and knowledge-sharing about EDI policies and practices, as well as concrete actions to create a more diverse scholarly community.